EKSTRAKSI DAN UJI STABILITAS ZAT WARNA DARI KULIT BUAH ALPUKAT (Persea americana Mill) DENGAN METODE SPEKTROSKOPI UV-VIS - Fauziah, Nadiya Ayu; Saleh, Chairul; -, Erwin (JURNAL ATOMIK, 2016)
The avocado skin fruit (Persea americana Mill) is one of species of Lauraceae family that had many benefits and efficiacy for human. Avocado is a woody plant, the life cycle can reach decades and were known to have potential as pigmen. The purpose of this study is to extract and determine the stability of pigmen from avocado skin fruit (Persea americana Mill) with UV-Vis Specroscopy methode. The extraction was done with soxhlet method using ethanol. The result of soxhlet was 142,13 gr avocado skin fruit dried powder was gained 88,85 gr ethanol extract. The ethanol extract of avocado skin dried powder was concentrated using rotary avoporator was gained 47,93 gr. The result phytochemical study, shown that ethanol coarse contained of Tannin compound, flavonoids and antosianin. The study stability of pigmen from avocado skin fruit (Persea americana Mill) extract was done to temperature effect were 40oC, 50oC, 60oC, 70oC and 80oC, pH effect were 3, 4, 5 and 6 and long storage effect were 1, 2, 3, 4 and 5 days at wave length 200-400 nm. The observational data were analyzed by ANOVA followed by Duncan test..Keywords: Persea americana Mill, Phytochemical , Stability of Pigmen